Transformasi Pendidikan Islam di Era Global: Tantangan Globalisasi, Integrasi Ilmu, dan Penguatan Karakter Berbasis Nilai Keislaman - Sukari, Sukari; Widyaningsih, Erna; Dewi, Rachma Rusdiana (Lembaga Yasin AlSys, 2026)
Islamic education in the global era faces major challenges due to the influence of globalization, the development of digital technology, and rapid sociocultural change, which together create a gap between the ideal of Islamic education as a builder of noble character and the reality of modern education that tends to be secular and materialistic. This study aimed to analyze the key issues confronting Islamic education in the global era and to formulate strengthening strategies to ensure its continued relevance and competitiveness. A qualitative approach was employed using a library research method through the review of books, scholarly journals, and policy documents addressing Islamic education and the challenges of globalization; data were collected using documentation techniques and analyzed through content analysis to identify core relevant themes. The findings indicate that Islamic education faces various critical issues, such as an identity crisis, the dichotomy between religious and general sciences, disparities in educational access, and the threat of radicalism, while at the same time holding strategic opportunities through knowledge integration, the use of digital technology, curriculum reform, and the strengthening of religious moderation. The study concludes that Islamic education needs to develop a new paradigm that is integrative, adaptive, and character-based in order to produce a generation that is faithful, knowledgeable, and globally competitive without losing its spiritual values, with theoretical implications for the development of contemporary Islamic education discourse and practical implications for policymakers and Islamic education providers in designing programs that are responsive to global dynamics.